Echocardiography for extracorporeal membrane oxygenation. Issue 2 (7th January 2022) - Hussey, Patrick T.; von Mering, Gregory; Nanda, Navin C.; Ahmed, Mustafa I.; Addis, Dylan R.
Abstract: Extracorporeal membrane oxygenation (ECMO) provides advanced cardiopulmonary life support for patients in cardiac and/or respiratory failure. Echocardiography provides essential diagnostic and anatomic information prior to ECMO initiation, allows for safe and efficient ECMO cannula positioning, guides optimization of flow, provides a modality for rapid troubleshooting and patient evaluation, and facilitates decision‐making for eventual weaning of ECMO support. Currently, guidelines for echocardiographic assessment in this clinical context are lacking. In this review, we provide an overview of echocardiographic considerations for advanced imagers involved in the care of these complex patients. We focus predominately on new cannulas and complex cannulation techniques, including a special focus on double lumen cannulas and a section discussing indirect left ventricular venting. Echocardiography is tremendously valuable in providing optimal care in these challenging clinical situations. It is imperative for imaging physicians to understand the pertinent anatomic considerations, the often complicated physiological and hemodynamic context, and the limitations of the imaging modality.